Caring for Students: What Teachers Have to Say. (3rd March 2014) - Garza, Rubén; Alejandro, Elba Armandina; Blythe, Tucker; Fite, Kathy
Abstract : In this exploratory qualitative study we examined teachers' perceptions of teacher behaviors that convey caring in upper elementary and middle school classrooms. Data collection included teacher interview, classroom observations, and teacher self-reflection. Major findings include specific caring behaviors perceived by teachers that are identified and described in four themes: (a) fostering a sense of belonging, (b) getting to know students personally, (c) supporting academic success, and (d) attending to physiological needs. Our findings contribute to a body of research on caring by including teachers' voices and illuminating an authentic approach in caring for students. Our description of caring behaviors and patterns of interactions demonstrate caring in ways that may not be congruent with the norm. Thus, our findings may provide new insight for educators to examine their personal ideology.